Removal of γ-HCH, 1, 4-Dichlorobenzene and trichloromethane from air via the adsorption of snow. (15th September 2019) - Wang, Nan; Liu, Hanfei; Kang, Chunli; Wang, Yuhan; Kunkun, Xiao; Tian, Tao
Abstract: Snow is an important reservoir of volatile and semi-volatile organic compounds. In this paper, the adsorption kinetics and thermodynamics of gamma-hexachlorocyclohexane (γ-HCH) and other two kinds of important pollutants in the environment, 1, 4-Dichlorobenzene ( p -DCB) and trichloromethane (TCM), were investigated by the adsorption experiment. The results suggest that γ-HCH adsorption capacity on snow is much higher than that of p -DCB and TCM. The adsorption kinetics of the three pollutants fit the pseudo-second-order kinetic equation, and their adsorption thermodynamics accord with Henry's linear adsorption model. The effect of common inorganic salts (Na2 SO4, Na2 CO3 and NaNO3 ) on adsorption was positive, the presence of inorganic salts promoted the adsorption of γ-HCH, p -DCB and TCM on the snow. The adsorption of γ-HCH on natural snow was at least 3.5 times greater than that on artificial snow. All the results indicate that snow in cold regions may be the significant reservoir of organic pollutants. Highlights: γ-HCH has the highest adsorption capacity on snow among three pollutants. Adsorption kinetics conforms to the pseudo second-order kinetic equation. Adsorption thermodynamics is consistent with Henry adsorption model. γ-HCH adsorption on natural snow is greater than that on artificial snow.